# SOLUTION: Solve x + y + z = 11 2x + y - z = 13 x = 2y

Algebra ->  -> SOLUTION: Solve x + y + z = 11 2x + y - z = 13 x = 2y      Log On

 Ad: Mathway solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Question 65601This question is from textbook An Incremental Development : Solve x + y + z = 11 2x + y - z = 13 x = 2yThis question is from textbook An Incremental Development Answer by praseenakos@yahoo.com(507)   (Show Source): You can put this solution on YOUR website!QUESTION: Solve x + y + z = 11 2x + y - z = 13 x = 2y ANSWER: x + y + z = 11 -----------------------(1) 2x + y - z = 13 -----------------------(2) x = 2y -------------------------------(3) Fron (2) we have, x = 2y. Substitute this value in (1) and (2) ==> 2y + y + z = 11 3y + z = 11 ------------------------(4) 2(2y) + y - z = 13 4y + y - z = 13 ==> 5y - Z = 13 -------------------------(5) Let's take (4) and (5) together, 3y + z = 11 ------------------------(4) 5y - Z = 13 ------------------------(5) _____________________________________________________________________________ Add (4) and (5) ====> 3y + z + 5y - Z = 11 + 13 ==> 8y = 24 Divide both sides by 8, ==> 8y/8 = 24/8 ==> y = 3 Substitute the value of y in equation (3) x = 2y ==> x = 2* 3 ==> x = 6 Input the values of x and y in equation (1) 6 + 3 + z = 11 ==> 9 + z = 11 Subtract 9 from both sides, ==> 9 + z - 9 = 11 - 9 ==> z = 2 so the solution is, x = 6 y = 3 z = 2 Hope you understood. Regards. praseenakos@yahoo.co.in